Where are they going? Directed cell movement in morphogenesis - Zimmermann, Frank (BioMed Central, 2001)
A report on the 'Cell and Tissue Morphogenesis' Spring Meeting of the British Societies for Cell and Developmental Biology, University of Sussex, Brighton, UK, 3-6 April, 2001.